Mobile phone usage and its perceived ill health effects: a cross sectional study in Chennai, India - Patki, Manoj B.; Arumugam, Balaji; Anusuya, Ganesh S.; Karthik, Recharla Chenchu; Mani, Ezhilvanan; Annamalai, Radhakrishnan (International Journal Of Community Medicine And Public Health, 2020)
Background: Smart phone usage is on the rise in India. Previous studies have attributed mobile phone usage to certain health problems. Not many studies have been done in the community in Chennai pertaining to ill health effects of mobile phone usage. Methods: This was a cross sectional study done on 213 participants of age >14 years of urban and rural field practice area of Tagore Medical College and Hospital in Chennai. The duration of the study period was from January to March 2019. Participants were interviewed by using a pretested questionnaire. House to house survey was done for data collection. Descriptive statistics and chi square test were done to compare the various variables. Results: Nearly 52% were females. Mean age was 30 years. The most common perceived ill health effects were eye symptoms (63%), headache (40%), and feeling irritable (25%).The major differences among urban and rural population in mobile phone usage were, playing games (50% vs 35%: p=0.019), listening to music (77.7% vs 54.5% : p=0.000), taking selfies (48.5% vs 36.4% : p=0.048). Urban people in the study were found to use mobile phones more for internet (77.7%), WhatsApp (77.7%), and Facebook (70%), than rural people which was found to be internet (61.8%), WhatsApp (58.2%), and Facebook (40%) and their respective p values were 0.009, 0.002, 0.000. Conclusions: Authors strongly recommend undertaking health education and health awareness activities regarding the ill health effects of mobile phone usage in the community.